2019
DOI: 10.1021/acs.cgd.9b00505
|View full text |Cite
|
Sign up to set email alerts
|

At the Interface of Isomorphous Behavior in a 3 × 3 Isomer Grid of Monochlorobenzamides: Analyses of the Interaction Landscapes via Contact Enrichment Studies

Abstract: The physicochemical properties of a 33 isomer grid of mono-chlorobenzamides (Clxx) are reported with comprehensive studies of their crystal structures and interaction environments (Clx = para-/meta-/ortho-chlorobenzoyl and x = para-/meta-/orthoaminopyridine substitutions). The nine compound Clxx series was synthesised from the three p-/m-/o-chlorobenzoyl chlorides and three p-/m-/o-aminopyridine isomers using standard synthetic procedures. Clxx exhibits some similarities to the related Fxx and Brxx congeners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(52 citation statements)
references
References 98 publications
(959 reference statements)
0
52
0
Order By: Relevance
“…The nine N -(chlorophenyl)pyridinecarboxamide crystal structures ( NxxCl ) are grouped in triads for structural comparisons with pertinent structural data presented in Tables 1 and 2 . Comparisons are made with the Clxx series 56 (as their amide-bridge reversed isomers) together with the related NxxF , 50 (methyl) NxxM , 51 and NxxBr analogues. 54 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The nine N -(chlorophenyl)pyridinecarboxamide crystal structures ( NxxCl ) are grouped in triads for structural comparisons with pertinent structural data presented in Tables 1 and 2 . Comparisons are made with the Clxx series 56 (as their amide-bridge reversed isomers) together with the related NxxF , 50 (methyl) NxxM , 51 and NxxBr analogues. 54 …”
Section: Resultsmentioning
confidence: 99%
“…Overall, 2D sheets interlock into a 3D structure by using 2 × (C13–H13···O1=C1) and 2 × (C1=O1···H13–C13) weak H-bonds per aggregate. This hydrate aggregation is similar to related benzamide hydrates with all strong hydrogen bonding donors and acceptors used ( e.g ., in Clpm· 2 H 2 O 75 and Clmm·H 2 O ( 56 )). The closest contacts with the para -chlorine Cl14 atom involve three H atoms (H23, H25, and H26) on symmetry related molecules but with all of the H···Cl14 distances larger than 3.0 Å.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have been dedicated to the rules and factors affecting the melting point that could be calculated as the quotient of enthalpy and entropy of melting (Carnelley, 1882;Beacall, 1928;Holler, 1948;Gavezzotti, 1995;Brown & Brown, 2000;Boese et al, 1999;Thalladi & Boese, 2000;Thalladi et al, 2000a,b,c;Katritzky et al, 2001;Bujak et al, 2008;Joseph et al, 2011;Podsiadło et al, 2012Podsiadło et al, , 2013Yalkowsky & Alantary, 2018;Gallagher et al, 2019). The studies showed that the location of substituents in molecules and their ability to form intermolecular interactions cannot be neglected when explaining the melting-point differences of isomers.…”
Section: Introductionmentioning
confidence: 99%